Composite magnetic flocculant and preparation method thereof

CN120247192BActive Publication Date: 2026-10-30QINGTIAN FUCHUN ZIGUANG SEWAGE TREATMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510268597.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2026-10-30
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

专利CN115947433B公开了一种粉煤灰纳米磁珠絮凝剂,利用粉煤灰、纳米二氧化硅、聚丙烯酰胺等原料来制备处理污水的絮凝剂,虽然该絮凝剂加入了粉煤灰废弃物,降低了生产成本,且整体絮凝效果良好,但是絮凝沉降时间长

Benefits of technology

(1)有效利用粉煤灰工业副产物,能够减少资源的浪费和废弃物的再生使用。(2)原料毒副作用极小,仅聚丙烯酰胺具有较弱毒性,但用量较少,可减少对环境的二次污染。(3)原料采用的粉煤灰价格低廉,而强磁性材料磁性纳米颗粒γ-Fe2O3和絮凝吸附效果较好的聚丙烯酰胺的价格虽然相对较高,但用量较少,原料所需价格相对较低,且制备方法仅包括将各组分加热搅拌以及干燥粉碎的过程,故制备方法绿色经济。(4)各原料配合使用可实现高效絮凝,絮凝效果佳,且利用磁性和磁场作用,可实现絮体的快速沉降。(5)突破了以往絮凝剂难以同时实现高效絮凝、快速沉降和低成本等所有优势的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of composite magnetic flocculants, belongs to sewage treatment technical field.Composite magnetic flocculants include the following components: fly ash 15-30 parts, magnetic nano particles gamma-Fe2O3 5-10 parts, poly L-cysteine 1-4 parts, calcium source 3-6 parts, polyacrylamide 0.5-1.5 parts.Fly ash is a kind of industrial waste, widely available, its application and flocculant preparation can significantly reduce production cost, and preparation method is simple, overall green economy.Composite magnetic flocculants are used for sewage treatment, with excellent treatment effect, can realize efficient flocculation, rapid settlement, control settlement time is within 3-8min.The application also discloses the preparation method of the flocculant, the raw materials are mixed step by step, then stirred under heating condition, and the process of drying and crushing, the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment technology, and specifically to a composite magnetic flocculant and its preparation method. Background Technology

[0002] Flocculation and sedimentation is the most common method for treating high-turbidity wastewater. By adding coagulants and flocculants, suspended particles are formed into larger flocs, accelerating particle settling. However, flocs mainly rely on their own gravity for settling, resulting in poor settling efficiency. When the water quality of high-turbidity wastewater is very complex, insufficient settling force often fails to overcome fluid resistance, hindering rapid settling. To improve settling momentum, magnetic, electrical, and microwave effects have been introduced into the wastewater clarification process. Among these, magnetic flocculation technology utilizes an external magnetic field to enhance the settling momentum of magnetic flocs. It is simple to operate, has high separation efficiency, and produces very little secondary pollution, making it highly suitable for the treatment of high-turbidity wastewater.

[0003] Fly ash is a fine ash collected from the flue gas after coal combustion and is a major solid waste discharged from coal-fired power plants. Its main components include inorganic minerals such as silicon dioxide, alumina, iron oxide, and calcium oxide. With the development of the power industry, the emission of fly ash has increased year by year, becoming one of the largest industrial wastes in my country. As an industrial by-product, fly ash has broad potential for resource utilization, such as its application in the preparation of flocculants for wastewater treatment. Fly ash is inexpensive and contains magnetic components such as magnetite and hematite. Using it as a magnetic seed can significantly reduce the preparation cost of flocculants. Furthermore, its porous structure and adsorption properties can remove heavy metal ions and organic matter from water.

[0004] Currently, there is considerable research on the preparation of flocculants for wastewater treatment using fly ash and other chemical reagents. Patent CN115947433B discloses a fly ash nano-magnetic bead flocculant, which uses fly ash, nano-silica, and polyacrylamide as raw materials to prepare a flocculant for wastewater treatment. Although the addition of fly ash waste reduces production costs and the overall flocculation effect is good, the flocculation and settling time is long. Patent CN104276643B discloses a method for preparing a magnetic flocculant using fly ash magnetic beads and polyacrylamide composites. This method includes the selection of magnetic beads from fly ash, ball milling and re-magnetic separation, preparation of a micro-magnetic bead suspension, composite swelling of micro-magnetic beads and polyacrylamide, and post-treatment unit processes. Compared with pure polyacrylamide, although the magnetic flocculant technology significantly improves the flocculation effect and settling speed, the preparation process is more complex, requires more equipment, and is more expensive.

[0005] While novel magnetic flocculants each have their advantages, they all face the challenge of simultaneously achieving high-efficiency flocculation, rapid sedimentation, and low cost. Therefore, it is necessary to continuously develop new composite magnetic flocculants that achieve efficient and rapid flocculation with green and economical preparation methods. Summary of the Invention

[0006] To address the shortcomings of existing flocculants, this invention aims to provide a composite magnetic flocculant. The composite magnetic flocculant uses fly ash, magnetic nanoparticles γ-Fe₂O₃, poly-L-cysteine, a calcium source, and polyacrylamide as its core components. The calcium source acts as a modifier for fly ash, enhancing its magnetic properties and adsorption energy while reducing production costs; the addition of sulfate further modifies it. Poly-L-cysteine ​​contains thiol groups, amino groups, carboxyl groups, and disulfide bonds, which can surface-modify the magnetic nanoparticles γ-Fe₂O₃, giving them better dispersibility, biocompatibility, and chemical stability. The addition of a small amount of polyacrylamide enhances the flocculation effect. The composite magnetic flocculant prepared by using these raw materials achieves efficient and rapid flocculation and significantly reduces production costs. Another objective is to provide a simple and environmentally friendly method for preparing the composite magnetic flocculant.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A composite magnetic flocculant comprises the following components: 15-30 parts fly ash, 5-10 parts magnetic nanoparticles γ-Fe2O3, 1-4 parts poly-L-cysteine, 3-6 parts calcium source, and 0.5-1.5 parts polyacrylamide.

[0008] Fly ash possesses a large specific surface area and abundant porous structure. Its surface also contains active groups such as aluminum, silicon, and iron, enabling it to adsorb suspended particles, organic matter, and heavy metal ions from wastewater, forming flocs that then precipitate. Calcium ions from the calcium source can react with silicates and aluminates in fly ash to generate hydration products with gelling properties. These hydration products further enhance the adsorption capacity of fly ash and help encapsulate pollutants in wastewater. Polyacrylamide is a water-soluble polymer with a long-chain structure and high molecular weight. Its long molecular chains act as bridges, connecting tiny particles in wastewater and linking them into larger flocs through physical entanglement. This "bridging" effect allows originally dispersed tiny particles to aggregate, forming large flocs that are easy to settle and filter. Fly ash also contains magnetic components, such as magnetite and hematite, which can be used as magnetic seeds. When combined with flocculants, they can rapidly aggregate colloidal particles in water to form dense, high-density composite magnetic flocs through charge neutralization, adsorption bridging, double-layer compression, and sweeping netting. However, the magnetic content in fly ash is relatively low, approximately 1-5%, and the magnetism is weak. Adding magnetic nanoparticles can enhance its magnetism, achieving the goal of using magnetism to rapidly aggregate and settle pollutants in wastewater. The addition of waste fly ash also reduces the use of strongly magnetic nanoparticle materials, significantly lowering production costs. Poly-L-cysteine ​​possesses a unique chemical structure and various excellent properties. Containing thiol groups, amino groups, carboxyl groups, and disulfide bonds, it can effectively modify γ-Fe₂O₃ nanocomposites, giving them better dispersibility, biocompatibility, and chemical stability. It can form chemical bonds with heavy metal ions for coordination or chelation, thereby achieving highly efficient adsorption.

[0009] Preferably, the composite magnetic flocculant is composed of the following raw materials in parts by weight: 20-25 parts fly ash, 7-8 parts magnetic nanoparticles γ-Fe2O3, 2-3 parts poly-L-cysteine, 4-5 parts calcium source, and 0.8-1.2 parts polyacrylamide.

[0010] Preferably, the calcium source is one or both of calcium chloride and lime.

[0011] Lime is a low-cost and readily available modifier, offering high cost-effectiveness in practical applications. Calcium chloride, on the other hand, exhibits stronger reactivity and can achieve better modification effects under certain specific conditions.

[0012] Preferably, the polyacrylamide is anionic polyacrylamide with a molecular weight of 8-15 million, cationic polyacrylamide with a molecular weight of 5-12 million, or nonionic polyacrylamide with a molecular weight of 9-12 million.

[0013] Polyacrylamide is a highly efficient flocculant; adding even a small amount can significantly enhance the flocculation effect of a system. The larger the molecular weight of polyacrylamide, the longer its molecular chain, and the more suspended particles it can adsorb. This high molecular weight polyacrylamide can more effectively capture and bridge tiny particles in water during flocculation, improving flocculation efficiency. However, when the molecular weight of polyacrylamide is too high, its molecular chain becomes excessively long, making it difficult to completely dissolve and disperse in water, which can negatively impact flocculation. Therefore, polyacrylamide with a molecular weight of several hundred to over ten million is more suitable for wastewater treatment.

[0014] Preferably, the composite magnetic flocculant further comprises, by weight: 2-5 parts sulfate, 1-2 parts dispersant and 0.5-1 parts surfactant.

[0015] Dispersants can prevent the re-agglomeration of modified fly ash particles and provide a uniform dispersion environment for the addition of subsequent components, while surfactants can modify the particle surface and enhance adsorption capacity, further improving the performance of flocculants.

[0016] Preferably, the mixture further comprises, by weight: 3-4 parts sulfate, 1.5-1.8 parts dispersant and 0.7-0.9 parts surfactant.

[0017] Preferably, the sulfate is one or two of sodium sulfate or gypsum, the dispersant is one or two of sodium hexametaphosphate or modified polyether dispersant, and the surfactant is one or two of oleic acid or Tween.

[0018] Sulfate ions in sulfates can react chemically with the active components in fly ash to form new chemical bonds. These bonds help fix pollutants in wastewater onto fly ash particles, thus achieving flocculation and sedimentation. Sodium hexametaphosphate is a commonly used inorganic dispersant with relatively low production costs and is widely available and easily accessible. Using a small amount of modified polyether dispersant can significantly improve the efficiency and quality of flocculants, thereby reducing overall costs to some extent. Oleic acid has good wetting and dispersing properties. Tween exhibits excellent emulsifying, dispersing, and stabilizing properties.

[0019] The present invention also employs another technical solution: A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium source and stir evenly, then slowly add sulfate and stir for 30-120 minutes. Finally, remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 6-12 hours. Then, unbound poly-L-cysteine ​​was removed by centrifugation and washing. (3) Mix the modified fly ash and dispersant evenly, then add the product obtained in step (2) and stir evenly. Finally, add the dispersant and surfactant and stir for 30-60 minutes to obtain a mixture. (4) The mixture is dried and pulverized to obtain a composite magnetic flocculant.

[0020] Fly ash particles are fine; pre-dispersing the fly ash in deionized water prevents agglomeration and ensures uniform distribution. Then, a calcium source is added. The calcium source can undergo ion exchange or complexation reactions with silicates and other components in the fly ash, improving its surface properties and making it easier to combine with other components. Similarly, magnetic nanoparticles are extremely fine and can be uniformly dispersed in deionized water to ensure a more complete reaction with poly-L-cysteine. Dispersants prevent the re-agglomeration of modified fly ash particles and provide a uniform dispersion environment for the subsequent addition of components, namely poly-L-cysteine-modified magnetic nanoparticles γ-Fe2O3, while also improving the stability and reaction efficiency of the flocculant. Polyacrylamide is a highly efficient flocculant; adding a small amount can significantly enhance the flocculation effect of the system. Surfactants can adjust the surface tension of the system, further optimizing the performance of the flocculant. Both are added last to avoid premature agglomeration of nanoparticles and fly ash.

[0021] Preferably, the stirring speed is 500-650 rpm.

[0022] Stirring too slowly will result in uneven mixing of materials, leading to excessively high local concentrations, which will affect product quality and greatly increase reaction time. Stirring too fast will cause materials to splash, damage the material structure, generate a lot of heat, wear out instruments and equipment, and reduce product quality.

[0023] Preferably, the stirring temperature in steps (1) and (2) is 30-60℃, the stirring temperature in step (3) is 30-40℃, and the drying temperature in step (4) is 60-80℃.

[0024] When modifying fly ash and surface-modifying magnetic nanoparticles γ-Fe2O3, a temperature range of 30-60℃ provides a moderate reaction rate and relatively uniform reaction. Lower temperatures promote the reaction between sulfates and calcium sources with fly ash while avoiding damage to the chemical structure or organic ligands caused by high temperatures. Appropriate temperatures also help to partially break down the glass network structure inside the fly ash, forming more pores and thus improving its adsorption performance. When adding dispersants and polyacrylamide, a lower temperature (30-40℃) helps to ensure uniform dispersion of the dispersants and surfactants, avoiding localized overheating and agglomeration caused by high temperatures. Polyacrylamide and other polymeric materials can maintain chemical stability within this temperature range, preventing degradation. Finally, during drying, a slightly higher temperature can accelerate drying and also prevent excessively high temperatures from causing degradation or damage to the chemical structure of the product.

[0025] The beneficial effects of this invention are as follows: (1) Effective utilization of fly ash industrial by-products can reduce resource waste and the recycling of waste. (2) The raw materials have minimal toxicity. Only polyacrylamide has weak toxicity, but the amount used is small, which can reduce secondary pollution to the environment. (3) The fly ash used as raw material is inexpensive, while the price of strong magnetic nanoparticles γ-Fe2O3 and polyacrylamide with good flocculation and adsorption effects is relatively high, but the amount used is small, so the raw material cost is relatively low. Moreover, the preparation method only includes heating, stirring and drying the components, so the preparation method is green and economical. (4) The combination of raw materials can achieve efficient flocculation with good flocculation effect. Furthermore, the rapid sedimentation of flocs can be achieved by utilizing magnetic and magnetic fields. (5) It overcomes the shortcomings of previous flocculants that could not simultaneously achieve all the advantages of efficient flocculation, rapid sedimentation and low cost. Detailed Implementation

[0026] The present invention will be further described below with reference to embodiments.

[0027] General Implementation Examples This embodiment provides a composite magnetic flocculant comprising the following components in parts by weight: 15-30 parts fly ash, 5-10 parts functionalized magnetic nanomaterial γ-Fe2O3, 1-4 parts poly-L-cysteine, 3-6 parts calcium source, 0.5-1.5 parts polyacrylamide, 2-5 parts sulfate, 1-2 parts dispersant, and 0.5-1 part surfactant.

[0028] In some embodiments provided by the present invention, the calcium source is one or both of calcium chloride or lime.

[0029] In some embodiments provided by the present invention, the polyacrylamide is anionic polyacrylamide with a molecular weight of 8 million to 15 million, cationic polyacrylamide with a molecular weight of 5 million to 12 million, or nonionic polyacrylamide with a molecular weight of 9 million to 12 million.

[0030] In some embodiments provided by the present invention, the sulfate is one or both of sodium sulfate or gypsum.

[0031] In some embodiments provided by this invention, the dispersant is one or both of sodium hexametaphosphate or modified polyether.

[0032] In some embodiments provided by the present invention, the surfactant is one or both of oleic acid or Tween.

[0033] This embodiment also provides a method for preparing the above-mentioned composite magnetic flocculant, including the following steps: (1) Disperse fly ash in deionized water, add calcium source and stir evenly, then slowly add sulfate and stir for 30-120 minutes. Finally, remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 6-12 hours. Then, unbound poly-L-cysteine ​​was removed by centrifugation and washing. (3) Mix the modified fly ash and dispersant evenly, then add the product obtained in step (2) and stir evenly. Finally, add the dispersant and surfactant and stir for 30-60 minutes to obtain a mixture. (4) The mixture is dried and pulverized to obtain a composite magnetic flocculant.

[0034] In some embodiments provided by this invention, the stirring speed is 100-650 rpm.

[0035] In some embodiments provided by the present invention, the stirring temperature in steps (1) and (2) is 30-60°C, the stirring temperature in step (3) is 30-40°C, and the drying temperature in step (4) is 60-80°C.

[0036] Example 1 A composite magnetic flocculant comprises the following components in parts by weight: 22.5 parts of fly ash, 7.5 parts of magnetic nanoparticles γ-Fe2O3, 2.5 parts of poly-L-cysteine, 3.5 parts of sodium sulfate, 4.5 parts of calcium chloride, 1 part of anionic polyacrylamide, 1.5 parts of sodium hexametaphosphate, and 0.8 parts of oleic acid.

[0037] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 50°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 500 rpm and a temperature of 50 ℃. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 40°C. Then add the product obtained in step (2) and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (4) Dry and pulverize the mixture at a drying temperature of 70°C to obtain a composite magnetic flocculant.

[0038] Fly ash possesses a large specific surface area and abundant porous structure, enabling it to adsorb suspended particles, organic matter, and heavy metal ions from wastewater. Its surface contains active groups such as aluminum, silicon, and iron, which can form charged active sites in water, binding with metal ions or organic matter in wastewater to form flocs that then precipitate. Modifying fly ash using a combination of calcium sources and sulfates not only enhances its chemical adsorption capacity but also improves its physical structure and surface properties, resulting in higher efficiency and better performance in wastewater treatment. These products not only increase the reactivity of fly ash but also enhance flocculation by forming fibrous or network structures. Sodium hexametaphosphate is a commonly used inorganic dispersant that can form stable complexes with polyvalent metal ions such as calcium and magnesium, effectively preventing particle aggregation and maintaining the stability and homogeneity of the system. Sodium sulfate and calcium chloride contain abundant sulfate and calcium ions, resulting in good modification effects. Anionic polyacrylamide is suitable for neutral or alkaline wastewater and can effectively flocculate suspended particles in wastewater.

[0039] Example 2 A composite magnetic flocculant comprises the following components in parts by weight: 15 parts coal ash, 5 parts magnetic nanoparticles γ-Fe2O3, 3 parts poly-L-cysteine, 4 parts gypsum, 5 parts lime, 1.2 parts cationic polyacrylamide, 1.8 parts modified polyether, and 0.9 parts Tween.

[0040] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 650 rpm and 30°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 650 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 650 rpm and a temperature of 30°C. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 650 rpm and a temperature of 40°C. Then add the product obtained in step (2) and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (4) Dry and pulverize the mixture at a drying temperature of 80°C to obtain a composite magnetic flocculant.

[0041] Cationic polyacrylamide exhibits superior flocculation effects on negatively charged suspended particles, making it particularly suitable for high-turbidity wastewater containing substantial amounts of organic matter. Modified polyether dispersants achieve efficient dispersion in the medium through the combined action of hydrophilic and lipophilic groups in their molecular structure. The reaction between lime and water releases a significant amount of heat, which can lower the stirring temperature, preventing excessive heat and violent reactions, and protecting the equipment. The main component of lime is calcium oxide, and these calcium ions can react with silicates and aluminates in fly ash to generate hydration products with gelling properties. Lime can also increase the alkalinity of fly ash, further enhancing its activity. The main component of gypsum is calcium sulfate, and sulfate ions can chemically react with the active components in fly ash to generate hydration products with gelling properties. These hydration products can fill the voids between fly ash particles, increasing the density and strength of the fly ash, while also enhancing its adsorption capacity. Gypsum also provides calcium ions, further improving the modification effect of fly ash.

[0042] Example 3 A composite magnetic flocculant comprises the following components in parts by weight: 30 parts coal ash, 10 parts magnetic nanoparticles γ-Fe2O3, 2 parts poly-L-cysteine, 1.5 parts sodium sulfate, 1.5 parts gypsum, 4 parts calcium chloride, 0.8 parts nonionic polyacrylamide, 1.5 parts sodium hexametaphosphate, and 0.7 parts oleic acid.

[0043] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 60°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 650 rpm and a temperature of 60 ℃. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 30°C. Then add the product obtained in step (2) and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (4) The mixture is dried and pulverized at a temperature of 60°C to obtain a composite magnetic flocculant.

[0044] Nonionic polyacrylamide is suitable for neutral or weakly alkaline wastewater and exhibits excellent flocculation performance. The main component of gypsum is calcium sulfate. Sulfate ions can chemically react with active components in fly ash (such as silica and alumina) to generate hydration products with gelling properties (such as silica sulfate and aluminum sulfate). These hydration products have better solubility and dispersibility in water and can fill the voids between fly ash particles, improving the density and strength of the fly ash and increasing its adsorption capacity. Simultaneously, sulfate ions can disrupt the original glassy phase structure of fly ash, making its surface loose and porous, exposing more active sites. These active sites can more effectively adsorb suspended solids, colloids, and other impurities in the water, improving flocculation efficiency.

[0045] Example 4 A composite magnetic flocculant comprises the following components in parts by weight: 20 parts coal ash, 7 parts magnetic nanoparticles γ-Fe2O3, 1 part poly-L-cysteine, 2 parts sodium sulfate, 1.5 parts calcium chloride, 1.5 parts lime, 0.5 parts anionic polyacrylamide, 0.5 parts sodium hexametaphosphate, 0.5 parts modified polyether, and 0.5 parts oleic acid.

[0046] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 550 rpm and 60°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 550 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 550 rpm and a temperature of 60 ℃. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 550 rpm and a temperature of 40°C. Then add the product obtained in step (2) and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (4) Dry and pulverize the mixture at a drying temperature of 70°C to obtain a composite magnetic flocculant.

[0047] Calcium ions (Ca) in calcium sources 2+ The calcium source may react chemically with active silicate and aluminate ions in fly ash to form compounds such as calcium silicate and calcium aluminate. These reactions may alter the original structure of fly ash, making its surface more porous and exposing more active sites, which is beneficial for adsorption and flocculation. The addition of a calcium source may disrupt the glassy phase structure of fly ash, transforming it into a more active crystalline phase structure. This structural change may increase the specific surface area and porosity of fly ash, thereby improving its adsorption performance and flocculation efficiency.

[0048] Example 5 A composite magnetic flocculant comprises the following components in parts by weight: 25 parts coal ash, 8 parts magnetic nanoparticles γ-Fe2O3, 4 parts poly-L-cysteine, 1 part sodium sulfate, 1 part gypsum, 1.5 parts calcium chloride, 1.5 parts lime, 1.5 parts cationic polyacrylamide, 2 parts sodium hexametaphosphate, 0.5 parts oleic acid, and 0.5 parts Tween.

[0049] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 50°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 500 rpm and a temperature of 50 ℃. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 35°C. Then add the product obtained in step (2) and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (4) The mixture is dried and pulverized at a temperature of 70°C to obtain a composite magnetic flocculant.

[0050] By combining calcium sources and sulfates to modify fly ash, the surface of the modified fly ash may carry more positive or negative charges. These charges can electrostatically adsorb oppositely charged impurity particles in water, thus achieving chemical adsorption. Modified fly ash may also have higher density or better settling properties, allowing it to settle more quickly in wastewater and more effectively remove suspended solids and colloids.

[0051] Comparative Example 1 A composite magnetic flocculant comprises the following components in parts by weight: 22.5 parts coal ash, 3.5 parts sodium sulfate, 4.5 parts calcium chloride, 1 part anionic polyacrylamide, 1.5 parts sodium hexametaphosphate, and 0.8 parts oleic acid.

[0052] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 50°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Mix modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 40°C. Add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (3) The mixture is dried and pulverized at a temperature of 70°C to obtain a composite magnetic flocculant.

[0053] The difference between this comparative example and Example 1 is that this comparative example does not include γ-Fe2O3 nanoparticles and poly-L-cysteine.

[0054] Comparative Example 2 A composite magnetic flocculant comprises the following components in parts by weight: 22.5 parts of fly ash, 7.5 parts of nanoparticles γ-Fe2O3, 3.5 parts of sodium sulfate, 4.5 parts of calcium chloride, 1 part of anionic polyacrylamide, 1.5 parts of sodium hexametaphosphate, and 0.8 parts of oleic acid.

[0055] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 50°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Mix modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 40°C. Then add nanoparticles γ-Fe2O3 and stir evenly. Finally, add anionic polyacrylamide and oleic acid and stir for 50 min to obtain a mixture. (3) The mixture is dried and pulverized at a temperature of 70°C to obtain a composite magnetic flocculant.

[0056] The difference between this comparative example and Example 1 is that this comparative example does not include poly-L-cysteine, which can modify the γ-Fe2O3 nanoparticles.

[0057] Comparative Example 3 A composite magnetic flocculant comprises the following components in parts by weight: 22.5 parts of fly ash, 7.5 parts of magnetic nanoparticles γ-Fe2O3, 2.5 parts of poly-L-cysteine, 3.5 parts of sodium sulfate, 4.5 parts of calcium chloride, 1.5 parts of sodium hexametaphosphate, and 0.8 parts of oleic acid.

[0058] A method for preparing a composite magnetic flocculant includes the following steps: (1) Disperse fly ash in deionized water, add calcium chloride, stir at 500 rpm and 50°C, stir evenly, slowly add sodium sulfate and stir for 60 min at 500 rpm, and finally remove excess liquid by filtration or centrifugation to obtain modified fly ash. (2) Magnetic nanoparticles γ-Fe2O3 were dispersed in deionized water, and a certain amount of poly-L-cysteine ​​solution was added and stirred for 8 hours at a stirring speed of 500 rpm and a temperature of 50 ℃. Unbound poly-L-cysteine ​​was then removed by centrifugation and washing. (3) Mix the modified fly ash and sodium hexametaphosphate evenly at a stirring speed of 500 rpm and a temperature of 40°C. Then add the product obtained in step (2) and stir evenly to obtain a mixture. (4) The mixture is dried and pulverized at a temperature of 70°C to obtain a composite magnetic flocculant.

[0059] The difference between this comparative example and Example 1 is that this comparative example does not contain the highly efficient flocculant anionic polyacrylamide.

[0060] Table 1 summarizes the raw material ratios used in Examples 1-5 and Comparative Examples 1-3.

[0061] Table 1 shows the raw material ratios used in Examples 1-5 and Comparative Examples 1-3.

[0062] Effect test The flocculation effect of Examples 1-5 and Comparative Examples 1-3 was tested. The test method involved using the flocculants obtained from Examples 1-5 and Comparative Examples 1-3 to treat oilfield wastewater under an external magnetic field. Oilfield wastewater, also known as oil-based drilling wastewater, mainly originates from drilling operations, produced water, and well washing water during oil extraction. Its characteristics include: containing various organic, inorganic, and microbial substances; the organic matter is mainly petroleum hydrocarbons, and the inorganic matter mainly includes various salts and heavy metals. In addition, the wastewater may also contain suspended solids such as clay particles, silt, and fine sand. Its composition is extremely complex, with extremely high oil and suspended solids content, and extremely high COD content, reaching thousands or tens of thousands, making treatment extremely difficult.

[0063] The test results obtained from Examples 1-5 and Comparative Examples 1-3 are shown in Table 2.

[0064] Table 2 Test results.

[0065] Test results.

[0066] As shown in Table 2, the present invention exhibits excellent flocculation effect and rapid settling time. In Examples 1-5, the total nitrogen removal rate and turbidity removal rate reached over 97%, while the total phosphorus removal rate, COD removal rate, heavy metal removal rate, and color removal rate all reached over 98%, all higher than the comparative example. Furthermore, the settling time was controlled within 3-8 minutes. Compared to the comparative example, the floc settling time was significantly accelerated. Therefore, the composite magnetic flocculant of the present invention can achieve beneficial effects such as efficient flocculation, rapid settling, and effective removal of organic matter and heavy metals, while significantly reducing production costs and causing minimal secondary pollution to the environment, making it both green and economical.

Claims

1. A method for preparing a composite magnetic flocculant, characterized in that, By weight, the composite magnetic flocculant comprises the following raw materials: 15-30 parts fly ash, 5-10 parts magnetic nanoparticles γ-Fe2O3, 1-4 parts poly-L-cysteine, 3-6 parts calcium source, 0.5-1.5 parts polyacrylamide, 2-5 parts sulfate, 1-2 parts dispersant and 0.5-1 part surfactant; Its preparation methods include: (1) Disperse fly ash in water, add calcium source and stir, then add sulfate and stir for 30-120 min, filter or centrifuge to obtain modified fly ash; (2) Disperse magnetic nanoparticles γ-Fe2O3 in water, add poly-L-cysteine ​​solution and stir for 6-12 h, then centrifuge and wash; (3) Mix the modified fly ash with the dispersant, add the product obtained in step (2) and stir, add polyacrylamide and surfactant and stir for 30-60 min to obtain a mixture; (4) Dry and pulverize the mixture.

2. The method for preparing the composite magnetic flocculant according to claim 1, characterized in that, By weight, fly ash 20-25 parts, magnetic nanoparticles γ-Fe2O3 7-8 parts, poly-L-cysteine ​​2-3 parts, calcium source 4-5 parts, and polyacrylamide 0.8-1.2 parts.

3. The method for preparing the composite magnetic flocculant according to claim 1 or 2, characterized in that, The calcium source is one or both of calcium chloride and lime.

4. The preparation method of the composite magnetic flocculant according to claim 1, characterized in that, The polyacrylamide is anionic polyacrylamide with a molecular weight of 8-15 million, cationic polyacrylamide with a molecular weight of 5-12 million, or nonionic polyacrylamide with a molecular weight of 9-12 million.

5. The method for preparing the composite magnetic flocculant according to claim 1, characterized in that, By weight, it contains 3-4 parts sulfate, 1.5-1.8 parts dispersant and 0.7-0.9 parts surfactant.

6. The method for preparing the composite magnetic flocculant according to claim 1, characterized in that, The sulfate is one or two of sodium sulfate and gypsum, the dispersant is one or two of sodium hexametaphosphate and modified polyether dispersant, and the surfactant is one or two of oleic acid and Tween.

7. The method for preparing the composite magnetic flocculant according to claim 5, characterized in that, The sulfate is one or two of sodium sulfate and gypsum, the dispersant is one or two of sodium hexametaphosphate and modified polyether dispersant, and the surfactant is one or two of oleic acid and Tween.

8. The method for preparing the composite magnetic flocculant according to claim 1, characterized in that, The stirring temperature in steps (1) and (2) is 30-60℃, the stirring temperature in step (3) is 30-40℃, and the drying temperature in step (4) is 60-80℃.

Citation Information

Patent Citations

  • A method for preparing magnetic flocculant by compounding fly ash magnetic beads and polyacrylamide

    CN104276643B

  • A kind of fly ash nano magnetic bead flocculant and preparation method thereof

    CN115947433B

  • Fly ash-based magnetic coagulant for treating lead-containing wastewater as well as preparation method, application and regeneration method of fly ash-based magnetic coagulant

    CN113735235A

  • Fly ash nano magnetic bead flocculant and preparation method thereof

    CN115947433A